Continuous Variable Quantum Teleportation in Beam-Wandering Modeled Atmosphere Channel - 张胜利 金晨辉 史建红 郭建胜 邹旭波 郭光灿 (Chinese physics letters, 2017)
We investigate the continuous variable quomtum teleportation in atmosphere channels. The beam-wandering mode/is employed to analyze the teleportation of the unknown single-mode coherent state. Two methods, one is deterministic by increasing the aperture size of the detecting device and one is probabilistic by entanglement distillation, are proposed to improve the teleportation fidelity in the presence of atmosphere noises.